P175 Fetal calf serum alternatives for application in tissue engineering. (1st November 2019) - Schwab, R; Helmert, T; Gebhard, S; Peters, K; Hasenburg, A; Heller, M; Brenner, W
Abstract : Introduction/Background: Tissue engineering is an emerging field with growing importance in oncological reconstructive surgery, as it may help to replace damaged or injured body tissue with compatible substitutes. For overcoming the initial loss of the tissue engineered substitutes, pre-vascularized tissue surrogates would be helpful to enable a rapid/fast/quick connection of the blood vessels of the recipient. In vitro, culture of tissue engineered body substitutes are performed with fetal calf serum (FCS). Nevertheless, for in vivo application in humans, human platelet lysates may successfully replace FCS. Methodology: Human umbilical vein endothelial cells (HUVEC) were cultured with FCS and with two commercially available human platelet lysates (MultiPl'30 and MultiPL'100, kindly provided by MacoPharma International GmbH) or one non-commercially available human platelet lysates (hPL) (manufactured by Max Planck Institute for Polymer Research Mainz) in different concentrations. Cell viability, proliferation and tube formation assays were conducted by using platelet lysates and compared with 20% FCS. Results: Proliferation and cell viability of HUVEC cultured for 72 hours with the distinct types of human platelet lysates in different concentrations were similar to those of the controls (cells cultured with 20% FCS). Capillary-like structures of HUVEC cultured in all platelet lysates were more effective than cultured in FCS. The induction of tube formation was most effective by using 5% MultiPL'30. However, the use of platelet lysates in concentrations between 2.5% and 5% were more effective than the cultivation in 20% FCS. Conclusion: To prevent tissue rejection or adverse effects like an allergic reaction, autologous cells should be cultivated with human platelet lysates. We showed that human platelet lysates can replace FCS in the in vitro cultivation process and, additionally, that these cells are able to form capillary-like structures as prerequisite for pre-vascularized tissue substitutes in humans. Disclosure: Roxana Schwab: I have received honoraria and expenses from Roche Pharma AG and AstraZeneca GmbH and funding by Geistlich Biomaterials. MultiPl'30 and MultiPL'100 were kindly provided by MacoPharma International GmbH and the human platelet lysates (hPL) were kindly provided by the Max Planck Institute for Polymer Research Mainz. Annette Hasenburg: I have received honoraria and expenses from AstraZeneca, FBA Frauenärzte BundesAkademie GmbH, KlarigoVerlag, MedConcept, Med public GmbH, Med update GmbH, Medicultus, Pfizer, Promedicis GmbH, Pierre Fabre Pharma GmbH, Softconsult, Roche Pharma AG, Streamedup! GmbH, Tesaro Bio Germany GmbH. I am consultant to PharmaMar, Promedicis GmbH, Pierre Fabre Pharma GmbH, Roche Pharma AG and Tesaro Bio Germany GmbH. I have received funded research from Celgene. Tania Helmert: I have no conflict of interest. Susanne Gebhard: I have no conflict of interest. Katharina Peters: I have no conflict of interest. Martin Heller: I have no conflict of interest. Walburgis Brenner: I have no conflict of interest.